PENGARUH LATIHAN BOX JUMP TERHADAP POWER OTOT TUNGKAI PADA TEAM BOLA BASKET PUTRA SMP AL-AZHAR SYIFA BUDI II PEKANBARU - Lubis, Septia Liza; Ramadi, Ramadi; Sulastio, Agus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The low ability of the physical condition of the men's basketball team SMP Al-Azhar Syifa Budi II Pekanbaru was the background of the problem of this research. This study aims to determine the effect of box jump training on leg muscle power. This research uses correlational research. The study population was the men's basketball team SMP Al-Azhar Syifa Budi II Pekanbaru, totaling 12 people. The research sample of the Men's Basketball Team SMP Al-Azhar Syifa Budi II Pekanbaru were 12 people, with a total sample technique. To measure the effect of Box Jump training on leg muscle power, the vertical jump test is used. The hypothesis of this study (1) There are effects of Box Jump training on leg muscle power in the Men's Basketball Team SMP Al-Azhar Syifa Budi II Pekanbaru. (2) There is a vertical jump ability on the men's basketball team SMP Al-Azhar Syifa Budi II Pekanbaru The data analysis technique used the produc moment correlation analysis and regression with α = 0.05 The results: (1) there is an effect of box jump training on leg muscle power, where it is obtained that tcount = 2.002> ttable = 1.782. (2) there is a vertical jump capability where L calculate = 0.1587> L table = 0.242. Based on the results of the study, it was found that there was a significant relationship between box jump training and leg muscle power in the basketball team SMP Al-Azhar Syifa Budi II Pekanbaru.Key Words: Box Jump, Power Muscle Lungs